Self-targeted fertilizer subsidies - Banda, Chimwemwe; De Weerdt, Joachim; Duchoslav, Jan; Jolex, Aubrey (International Food Policy Research Institute, 2022)
If Malawi’s fertilizer subsidy program aims to increase food security in the country, it should strive to target the most productive farmers. Subsidy levels can be set to self-target this group of farmers. This would maximize output achieved with subsidized fertilizer and eliminate the need for costly and error-prone top-down targeting. Maximizing the productive capacity of the AIP In a previous policy note, we argued that by setting the farmer contribution to fertilizer subsidized under that Affordable Inputs Programme (AIP) so that farmer demand matches what the program can supply, the government can maximize the total amount of fertilizer available for distribution under the program (Banda et al.,2022). In this note, we argue that a second advantage of this pricing strategy is that it ensures that each subsidized bag of fertilizer has the largest possible yield response, thus maximizing the additional amount of food produced through the program.